Dose Effect Evaluation and Therapeutic Window of the Neuro-EPO Nasal Application for the Treatment of the Focal Ischemia Model in the Mongolian Gerbil - Iliana Sosa Teste; Yuneidys Mengana Tamos; Yamila Rodríguez Cruz; Adriana Muñoz Cernada; Janette Cruz Rodríguez; Nelvis Subirós Martínez; Rosa Maria Coro Antich; Alina González-Quevedo; Julio Cesar García Rodríguez (The Scientific World Journal)
Cerebrovascular disease is the third leading cause of death and the leading cause of disability in Cuba and in several developed countries. A possible neuroprotective agent is the rHu-EPO, whose effects have been demonstrated in models of brain ischemia. The Neuro-EPO is a derivative of the rHu-EPO that avoids the stimulation of erythropoiesis. The aim of this study was to determine the Neuro-EPO delivery into the central nervous system (CNS) to exert a neuroprotective effect in cerebral ischemia model of the Mongolian gerbil. The Neuro-EPO in a rate of 249.4 UI every 8 hours for 4 days showed 25% higher viability efficacy (𝑃>0.01), improving neurological score and behavior of the spontaneous exploratory activity, the preservation of CA3 areas of the hippocampus, the cortex, and thalamic nuclei in the focal ischemia model of the Mongolian gerbil. In summary, this study, the average dose-used Neuro-EPO (249.4 UI/10 μL/every 8 hours for 4 days), proved to be valid indicators of viability, neurological status, and spontaneous exploratory activity, being significantly lower than that reported for the systemically use of the rHu-EPO as a neuroprotectant. Indeed, up to 12 h after brain ischemia is very positive Neuro-EPO administration by the nasal route as a candidate for neuroprotection.